2011
DOI: 10.1530/eje-11-0132
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts in osteoporosis: past, emerging, and future anabolic targets

Abstract: Objective: Age-related bone loss is associated with significant changes in bone remodeling characterized by decreased trabecular and periosteal bone formation relative to bone resorption, resulting in bone fragility and increased risk of fractures. Prevention or reversal of age-related decrease in bone mass and increase in bone fragility has been based on inhibition of bone resorption using anticatabolic drugs. The current challenge is to promote osteoblastogenesis and bone formation to prevent age-related bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
147
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(157 citation statements)
references
References 144 publications
(133 reference statements)
6
147
0
4
Order By: Relevance
“…The majority of these new treatments have been directed at inhibition of bone resorption, whereas anabolic compounds in use or under investigation remain scarce. (1,3) An effective bone anabolic agent would induce bone formation by stimulating osteoblast activity, by protecting osteoblasts against premature death, and by promoting the differentiation of MSC down the osteoblast rather than the adipocyte lineage. (1) In fact, several studies have demonstrated that it is possible to stimulate osteoblast differentiation at the expense of adipogenesis using compounds such as parathyroid hormone, (18) interferon gamma, (19,20) and strontium ranelate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of these new treatments have been directed at inhibition of bone resorption, whereas anabolic compounds in use or under investigation remain scarce. (1,3) An effective bone anabolic agent would induce bone formation by stimulating osteoblast activity, by protecting osteoblasts against premature death, and by promoting the differentiation of MSC down the osteoblast rather than the adipocyte lineage. (1) In fact, several studies have demonstrated that it is possible to stimulate osteoblast differentiation at the expense of adipogenesis using compounds such as parathyroid hormone, (18) interferon gamma, (19,20) and strontium ranelate.…”
Section: Discussionmentioning
confidence: 99%
“…(1,3) An effective bone anabolic agent would induce bone formation by stimulating osteoblast activity, by protecting osteoblasts against premature death, and by promoting the differentiation of MSC down the osteoblast rather than the adipocyte lineage. (1) In fact, several studies have demonstrated that it is possible to stimulate osteoblast differentiation at the expense of adipogenesis using compounds such as parathyroid hormone, (18) interferon gamma, (19,20) and strontium ranelate. (21) The active metabolite of vitamin D, 1,25(OH) 2 D 3 , has also been shown to stimulate bone formation by promoting osteoblastogenesis (12) and inhibiting adipogenesis (17) in a murine model of age-related bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulations of osteoclast and osteoblast activities are associated with a range of pathological diseases such as osteoporosis which is characterized by low bone mass and microarchitectural deterioration of bone tissue, with a consequent increase in bone fragility [20,21]. Due to the increasing need for anabolic therapies to prevent age-related bone loss, research has been focused over the last decade on molecular mechanisms regulating osteoblast function in postnatal remodeling [20][21][22]. For instance, Runx2 and Osx have been found to regulate osteoblast function in adult bone in addition to their primarily established role in osteoblastogenesis [23,24].…”
Section: Discussionmentioning
confidence: 99%